Genital tuberculosis and infertility - Shende, Prajakta; Valecha, Shalini Mahana; Gandhewar, Manisha; Dhingra, Diwija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: An analytical study to diagnose genital tuberculosis, using various modalities, it`s treatment options and fertility outcomes in infertile labour class women. Methods: A prospective study, where 120 women, presented to hospital due to infertility were subjected to hystero-laparoscopy over 36 months. Endometrium sent for TB-PCR and HPR. Those diagnosed with GTB were given Anti-Tubercular Drugs as per standard regimes and their fertility outcome was studied. Results: Out of 120 women, 32(27%) were diagnosed with GTB using accepted clinical criteria, TB-PCR and endometrial HPR. 30 of these 32 were diagnosed by HLscopic picture (94%) alone, 18 by positive endometrial TB-PCR (58%) and another 3 by HPR (10%). Among 32 women treated, 9(28%) conceived after treatment. Conclusions: High incidence of GTB amongst the labour class warrants strong suspicion and early diagnosis using hystero-laparoscopy and prompt treatment to minimize the short and long-term effects of GTB on fertility.